Diffusion of population under the influence industrialization in a twin‐city environment - Dhar, J.; Singh, H. (Mathematical Modelling and Analysis, 2004)
A mathematical model of a living population in a twin‐city is proposed. Here populations are migrating from one place to another for their resource and settlement under the influence of industrialization. The long term effect of industrialization on the movement of human population is considered in two adjoining cities. It is shown that the steady state distribution of population is positive, continuous, monotonic and the system is stable under certain set of conditions. Further, numerical solution of the steady state distributions of population and industrialization are shown by taking particular values of the parameters. Populiacijos difuzija miestų-dvynių aplinkoje, esant industralizacijos poveikiui Santrauka. Straipsnyje pasiūlytas populiacijos dinamikos miestuose-dvyniuose matematinis modelis. Daroma preilaida, kad populiacija migruoja iš vienos vietos į kitą industralizacijos poveikyje. Tiriamas ilgalaikis industralizacijos poveikis žmonių judėjimui dviejuose gretimai esančiuose miestuose. Įrodyta, kad esant išpildytoms tam tikroms sąlygoms, nusistovėjęs rėžimas yra tolydus, monotoniškas ir stabilus. Taip pat pateiktas skaitiniais metodais gautas stacionarusis pasiskirstymas, esant pasirinktam parametrų rinkiniui. First Published Online: 14 Oct 2010